The effect of carbohydrate gel consumption on elite mountain bikers time to exhaustion and blood glucose metabolism - Beyleroğlu, Malik (Progress in Nutrition, 2019)
Study Objectives: In athletes, additional carbohydrate (CHO) uptake is important during submaximal and high-intensity exercise and competitions where the cost of metabolism exceeds endogenous carbohydrate depots. The aim of this study was to investigate the effects of carbohydrate gel consumption on glucose concentration and exercise time to exhaustion of elite mountain bikers. Methods: 20 mountain bikers (22,5 Å} 2,64 years; 67,4 Å} 5,44 kg; 174,7 Å} 4,59 cm) performed bicycle ergometer with increasing overload test at 48 hours intervals. The experimental group was given 42 g of carbohydrate gel 20 minutes before test and control group was not consumed carbohydrate gel. In addition, the glucose levels of the athletes were followed with blood samples taken before and after the tests. Results: The averages of glucose levels and exhaustion times were higher according to the carbohydrate gel consumption (p